Live of East Timorese Ex-Refugees: Past Trauma, the Role of Catholic Church, and Digital Technology - Dewi Puspita Rahayu; Wida Ayu Puspitosari (BELIEF: Sociology of Religion Journal, 2023)
This research undertakes an ethnographic exploration of the intricate impact of historical trauma on individuals hailing from Timor-Leste, specifically those who underwent forced migration during the tumultuous events surrounding the 1999 referendum. By centering on the life trajectories of Timor-Leste's former residents across multiple generations, the study delves into the complex interplay of trauma, economic challenges, the role of catholic church and the dynamic role played by digital technology in the lives of those who sought refuge in Nusa Tenggara Timur, Indonesia as the coping mechanisms adopted by these individuals as they navigate the profound traumas arising from the conflict. Additionally, the study aims to examine their resilience in the face of adversities, particularly during the challenging times of the COVID-19 pandemic. Furthermore, it seeks to unravel the intricate ways in which digital technology, encompassing smartphones and social media platforms, has become an influential factor in shaping their intricate life trajectories. Through a nuanced exploration of these elements, the research endeavours to contribute valuable insights into the multifaceted dimensions of the post-traumatic experiences of this community and the evolving role of technology in their coping mechanisms and adaptation strategies.